2014
DOI: 10.1111/cdoe.12117
|View full text |Cite
|
Sign up to set email alerts
|

Dental attendance among adult Finns after a major oral health care reform

Abstract: The use of oral health care services rose and age did not seem to be a barrier to the use of oral health care services after the reform, as was the aim of the reform. No change in the association of household income with the use of oral health care services was seen after the OHCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 25 publications
1
43
0
2
Order By: Relevance
“…Our results were similar to another Finnish study where data were gathered by repeated postal questionnaires in 2001, 2004 and 2007 [16]. However, in our study, the last measurement point was 4 years later than in the questionnaire study, thus giving a more up-to-date picture.…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar to another Finnish study where data were gathered by repeated postal questionnaires in 2001, 2004 and 2007 [16]. However, in our study, the last measurement point was 4 years later than in the questionnaire study, thus giving a more up-to-date picture.…”
Section: Discussionsupporting
confidence: 89%
“…() as the main predictor of oral health behaviour. A study of dental attendance amongst adult Finns also found perceived need for care to be a predictor of use of dental services in logistic regression analysis (Raittio, Kiiskinen, Helminen, Aromaa, & Suominen, ). Frequency of participants with regular dental visiting habits was similar to reports from the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two studies examined the major oral health care reform introduced in Finland between 2001 and 2002 [14,15]. This reform led to the opening of the Public Dental Services (PDS) and extended subsidies for private dental services to all adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By 2004, when subsidies had been extended to the entire adult population, this figure increased to almost every second adult. In three consecutive surveys of the Finn population (2001,2004,2007), Raittio et al [15] showed that between 2001 and 2007 the percentage of respondents who regularly sought dental care rose. In particular, the proportion of respondents who used the Public Dental Services increased, while the average number of visits to private dentists decreased between 2001 and 2007.…”
Section: Literature Reviewmentioning
confidence: 99%